2010
DOI: 10.1186/bcr2472
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression profiling of peripheral blood cells for early detection of breast cancer

Abstract: IntroductionEarly detection of breast cancer is key to successful treatment and patient survival. We have previously reported the potential use of gene expression profiling of peripheral blood cells for early detection of breast cancer. The aim of the present study was to refine these findings using a larger sample size and a commercially available microarray platform.MethodsBlood samples were collected from 121 females referred for diagnostic mammography following an initial suspicious screening mammogram. Di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
105
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 102 publications
(112 citation statements)
references
References 34 publications
5
105
2
Order By: Relevance
“…Moreover, it has been suggested that blood-based GEP can be used as a powerful tool for early diagnosis of certain solid cancer entities, [32][33][34][35][36] as well as infectious, 37,38 autoimmune, 39,40 and neurodegenerative 41 disease. Nevertheless, prospective clinical studies are still needed to validate these promising but still preliminary results in larger cohorts of patients or in individuals at risk for the respective diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it has been suggested that blood-based GEP can be used as a powerful tool for early diagnosis of certain solid cancer entities, [32][33][34][35][36] as well as infectious, 37,38 autoimmune, 39,40 and neurodegenerative 41 disease. Nevertheless, prospective clinical studies are still needed to validate these promising but still preliminary results in larger cohorts of patients or in individuals at risk for the respective diseases.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, specific blood transcriptional signatures were defined in adult volunteers challenged with specific respiratory viruses (11). Analysis of host transcriptional profiles has also been applied to the diagnosis of inflammatory and hematological diseases (12)(13)(14)(15), including the identification of potential biomarkers for specific disease entities (5).…”
mentioning
confidence: 99%
“…75 It would be very useful to develop new mechanisms to monitor the transcriptome expression pattern based on the use of noninvasive biological fluids. [76][77][78] As the composition of nucleic acids (specifically RNA) reflect in most cases the nature and origin of the parental cell, exosomes may be considered valuable carriers of cell-specific information because their content provides an insight glance of the proteins being transcribed in the original tissue. [79][80][81] In this manner, exosomes may be used in the clinic to achieve early diagnostics and prognosis information, but also to stratify and separate patients into different clinical categories in order to determine specific targeted therapies.…”
Section: Exosomes As Novel Cancer Biomarkersmentioning
confidence: 99%